Investigation of the effects of nozzle exit mach number and nozzle pressure ratio on axisymmetric flow through suddenly expanded nozzles - Khan, Sher Afghan; Mohiuddin, M; Saleel, Ahmad C; G M, Fharukh (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Computational Fluid Dynamics simulations were carried out using ANSYS FLUENT for suddenly expanded flow through the convergent-divergent nozzle and a suddenly expanded duct. The Length-to-Diameter ratio of 10 for the duct was used in the analysis. Also, an Area Ratio between CD Nozzle exit area and Duct Area was used to be 1.6. The effects of Nozzle Exit Mach number and the Nozzle Pressure Ratios were evaluated by conducting the simulations for Nozzle Exit Mach numbers: 1.87, 2.25 and 2.58. For each Mach number then, Nozzle Pressure Ratios of 3, 5, 7, 9, and 11 were set respectively. Making a total of 15 cases. All the cases were simulated using the k-ω turbulence model. Simulated results agree with the experimental data. From the analysis, it is clear that the Nozzle Exit Mach number and Nozzle Pressure Ratio have a direct effect on the expanded flow exiting the nozzle.